(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed at identifying the degree of availability of performance measurement indicators at Al-Quds Open University in the light of administrative quality from the point of view of the administrators. The study used the analytical descriptive method and the questionnaire as a study tool consisting of 30 paragraphs divided into six fields: (administrative leadership, quality and development, , Management information systems, monitoring and performance evaluation, beneficiary satisfaction). The questionnaire was applied to a random sample of the owners of administrative positions in the Gaza Strip. The most important findings of the study were that the responses of the sample of the study on the degree of availability of performance measurement indicators at Al-Quds Open University in light of administrative quality from the point of view of the administrators came to a great extent. The total score for the six domains (3.96), with a relative weight of 79.2 The results showed that there were no statistically significant differences at (0.05 α ≤) between the average of the sample of the study sample on the degree of availability of performance measurement indicators at Al-Quds Open University in light of the administrative quality due to gender variable and the existence of statistically significant differences between The responses of the study sample individuals are attributed to the absentee Years of service was in favor of the category (more than 10 years).